COMPUTATIONAL THINKING IN EDUCATION a pedagogical perspective. - Yadav, Aman.; Berthelsen, Ulf Dalvad ([S.l.] : ROUTLEDGE, 2021)
Computational Thinking in Education explores the relevance of computational thinking in primary and secondary education. As today's school-aged students prepare to live and work in a thoroughly digitized world, computer science is providing a wealth of new learning concepts and opportunities across domains. This book offers a comprehensive overview of computational thinking, its history, implications for equity and inclusion, analyses of competencies in practice, and integration into learning, instruction, and assessment through scaffolded teacher education. Computer science education faculty and pre- and in-service educators will find a fresh pedagogical approach to computational thinking in primary and secondary classrooms.
Keywords: Educational psychology; Educational technology; EDUCATION / Computers & Technology; EDUCATION / Distance Education & Learning; EDUCATION / Elementary